Damage Analysis Of Turbo Charger On Main Engine at KM. LEUSER - Andi Hendrawan; Lusiani; Aji Kusumastuti Hendrawan; Sri Pramono (LPPM AKMI SUAKA BAHARI CIREBON, 2023)
A centrifugal compressor known as a turbocharger is powered by a turbine powered by exhaust fumes from moving vehicles. Usually used in internal combustion engines to increase the air pressure entering the engine and increase engine efficiency. The main benefit of turbochargers is that they provide a significant increase in engine power for just a little extra weight. The research was carried out by direct observation and then recorded the damage that occurred. The results show that damage to the turbocharger includes damage to rotation, damage to the bearings, and damage as a result of the main engine. To avoid damage, adequate maintenance is needed so that ship components will last longer.